2012
DOI: 10.1007/s10877-012-9379-4
|View full text |Cite
|
Sign up to set email alerts
|

The utility of bispectral index monitoring for sedated patients treated with low-dose remifentanil

Abstract: The aim of the present study was to determine the effect of low-dose remifentanil on the monitoring quality of the Bispectral index for mechanically ventilated patients. Twelve patients who underwent elective surgery and required mechanical ventilation post-operatively were enrolled in this study with written informed consent. Eligible patients were divided into two groups. Patients in the remifentanil group received low-dose remifentanil (0.05-0.125 μg/kg/min) and propofol (1-3 mg/kg/h). Patients in the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Patients with lower remifentanil infusion rates showed an increase in heart rate, mean arterial pressure, and BIS index during intubation, which stand in line with the observations made by Iselin-Chaves et al [ 38 ], who described an inverse correlation between BIS index variability and level of analgesia. In contrast to that, Kato et al [ 39 ] calculated clearly a better correlation between the RASS Score and the BIS index when low-dose remifentanil was administered in addition to propofol. In this study, high variable BIS index values were observed at almost the same serum concentrations of sufentanil (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…Patients with lower remifentanil infusion rates showed an increase in heart rate, mean arterial pressure, and BIS index during intubation, which stand in line with the observations made by Iselin-Chaves et al [ 38 ], who described an inverse correlation between BIS index variability and level of analgesia. In contrast to that, Kato et al [ 39 ] calculated clearly a better correlation between the RASS Score and the BIS index when low-dose remifentanil was administered in addition to propofol. In this study, high variable BIS index values were observed at almost the same serum concentrations of sufentanil (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…Assumption of the correlation between BIS and OAA/S was estimated to be 0.7, as reported previously. 17 We also sought to detect the effect size of correlation with 5% a-error and 80% statistical power. Thus, we calculated that 15 patients were needed for each group, with an estimated dropout rate of 10%.…”
Section: Discussionmentioning
confidence: 99%
“…In the remifentanil group BIS and RASS was found to be correlated with each other, but no correlation was found between the two in the other group (18). We also evaluated patients using remifentanil infusion to achieve sedation in our study, and found a correlation between RASS and BIS.…”
Section: Resultsmentioning
confidence: 68%